Outcome-based Education and Constructivism Synergy Challenges and Possibilities - Murthy, C.G. Venkatesha (JOURNAL OF INDIAN EDUCATION, 2016)
The author has discussed Spady’s Outcome-based Education (OBE) which embodies the idea that the best way to learn is to first determine what needs to be achieved as outcomes of an educational programme. Once this is done, the strategies, processes and techniques can be put in place to achieve the targeted exit goal. It discusses the OBE philosophy, aims, principles, assessment criteria and benefits. Also discussed is the constructivist perspective as could be superimposed on OBE, and presents challenges and possibilities to focus on OBE using the lens of constructivism.